Backwash of uncertainty : exploitation or service? - Sumpter, Cameron (2020)
Blame games and misinformation during the pandemic are both highlighting and deepening divisions. While subversive groups appeal to frustrations and exploit gaps in state-led responses, civil society organisations are stepping in to provide where the state falls short.